PENGARUH ANAK ADHD TERHADAP INTERAKSI SOSIAL DAN PEMBELAJARAN DI SDS SEJAHTERA WAY KANDIS BANDAR LAMPUNG - Carollines, Agatha Famela (LPPM STKIP PGRI Bandar Lampung, 2019)
The purpose of this study was to determine the problems of guidance and counseling at SDS Sejahtera Bandar Lampung and to determine the concentration of learning ADHD children given by parents and class teachers. The method used is qualitative. The counseling guidance approach applied at SDS Sejahtera is like a special approach such as sitting next to the teacher, emotional guidance and giving advice. The techniques used by teachers and researchers are test techniques and non-test techniques (observation, interviews, and documentation). The case subjects in the study were children with ADHD aged 10 years, grade 4 years ago, and now they are 11 years old in grade 5. Participant subjects were teachers and parents. The concentration of learning is shown by the behavior of not listening to the teacher’s orders, teasing his friends and teachers, disturbing friends, even committing acts of violence such as hitting, pinching, injuring, throwing tantrums and screaming, scribbling on the blackboard, not being able to study in groups and interacting with surrounding environment. Handling guidance provided by teachers and parents is such as occupational therapy (doing activities or daily activities independently, physical exercise, and brain balance), talking, and nerve massage.